2018
DOI: 10.1007/s10103-018-2677-4
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal agent of silver nanoparticles activated by diode laser as light source to reduce C. albicans biofilms: an in vitro study

Abstract: Candida albicans is a normal flora caused fungal infections and has the ability to form biofilms. The aim of this study was to improve the antifungal effect of silver nanoparticles (AgNPs) and the light source for reducing the biofilm survival of C. albicans. AgNPs were prepared by silver nitrate (AgNO 3) and trisodium citrate (Na 3 C 6 H 5 O 7). To determine the antifungal effect of treatments on C. albicans biofilm, samples were distributed into four groups; L + P+ was treatment with laser irradiation and Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…They may also act against biofilms by their intrinsic bioactivity or as nanocarriers (drug delivery systems) [42]. There are a few studies that present the inhibitory effect of AgNPs on biofilm formation, especially for C. albicans [43][44][45][46], with one study even indicating a dose-dependent inhibitory effect on biofilm formation and against pre-formed biofilms [47]. Another recent study [48] demonstrated dose-dependent and size-dependent antibiofilm activity for AgNPs, with the smaller size AgNPs (7.0 ± 1.6 nm) being more effective.…”
Section: Discussionmentioning
confidence: 99%
“…They may also act against biofilms by their intrinsic bioactivity or as nanocarriers (drug delivery systems) [42]. There are a few studies that present the inhibitory effect of AgNPs on biofilm formation, especially for C. albicans [43][44][45][46], with one study even indicating a dose-dependent inhibitory effect on biofilm formation and against pre-formed biofilms [47]. Another recent study [48] demonstrated dose-dependent and size-dependent antibiofilm activity for AgNPs, with the smaller size AgNPs (7.0 ± 1.6 nm) being more effective.…”
Section: Discussionmentioning
confidence: 99%
“…Laser has a coherent and monochromatic beam, so its energy is more focused than other conventional light sources [14]. One of the laser interactions with tissue is the photochemical effect.…”
Section: Introductionmentioning
confidence: 99%
“…The light source used is a blue diode laser with a wavelength (403,000±0.007) nm and power (27.65±0.01) mW, suitable with the endogenous photosensitizer spectrum of bacteria. 15 The characterization results showed the stability of the laser intensity at (300,000±0.005) seconds after being turned on. Laser irradiation on biofilms was carried out for 30 s, 60 s, 90 s, 120 s and 150 s. The value of the density of the laser energy is calculated using Eq.…”
Section: Methodsmentioning
confidence: 93%
“…The combination of light at certain wavelengths with photosensitizers in antimicrobial photodynamics will produce radical reactive oxygen species (ROS) products that can cause bacterial cell lysis. 15 Zanin et al conducted a study to demonstrate the effectiveness of PDI in reducing the biofilm of Streptococcus mutans bacteria using LEDs and HeNe lasers. 16 The biofilm used has a variation in age of 3 days, 7 days and 10 days.…”
Section: Introductionmentioning
confidence: 99%